Development of an augmented reality integrated Problem-Solving Laboratory Model (PSLab-AR) for electricity concepts to enhance the students' understanding of concepts - Ali Ismail; Demmy Dharma Bhakti; Lasmita Sari; Lula Dwi Kemalia; Saprudin Saprudin (Momentum: Physics Education Journal, 2024)
This research aims to develop a product in the form of an integrated Augmented Reality Problem Solving Laboratory (PSLab-AR) model. The research method used in this research is research and development because it is in line with the main output of this research. The research design used consists of the Define, Design, Develop and Disseminate stages. Participants in this research consisted of three groups: the first group was two elementary school teachers at the define stage, three science education experts at the development stage, and 25 fifth grade students at the dissemination stage. This research uses a CVI validation sheet and 10 questions on students' conceptual understanding. Based on the needs analysis at the definition stage, PSLab-AR is needed to assist science learning in elementary schools, especially in providing an interesting representation of the abstract concept of electricity. During the Design and Development stage, we found that the PSLab-AR framework passed expert evaluation by producing a framework consisting of preparation stages (understanding the practicum objectives, reading materials, and answering questions), problem solving (studying the problem context, formulating the problem, and creating prediction), exploration (determining tools and materials, understanding tool function, and creating procedures), measurement, data analysis, and drawing conclusions. At the dissemination stage, the research results showed that the Augmented Reality Integrated Problem Solving Laboratory model could increase students' conceptual understanding by 27.6 with an N-gain value of 0.610 in the medium category.